The Covid-19 Pandemic And Its Positive Impact On The Growth Of The Digital-Based Creative Industry In Indonesia - Solehudin, Rd. Heri; Budiarti, Erna; El Khuluqo, Ihsana; Haris, Abdul; Mustomi, Otom (AMCA Journal of Community Development, 2025)
The COVID-19 pandemic that has spread throughout the world since early 2020 has had a major impact on various sectors, including the digital creative industry in Indonesia. This research aims to analyze the positive impact of the COVID-19 pandemic on the growth of digital-based creative industries in Indonesia. In a challenging situation, digital-based creative industries demonstrated rapid adaptation and significant innovation, capitalizing on the increasing need for digital services and home entertainment. In Indonesia, this pandemic has not only brought challenges but also new opportunities, especially for digital-based creative industries. This research aims to explore the positive impact of the COVID-19 pandemic on the growth of the digital creative industry in Indonesia. This research uses a qualitative approach. A qualitative approach is used to understand the perspectives of stakeholders and creative industry players. Participants in this research are creative industry players in several big cities in Indonesia (Jakarta, Bandung, Yogyakarta, Surabaya, and Makasar), as well as stakeholders from government, creative industry associations, and academia. Secondary data was taken from the official report of the Ministry of Tourism and Creative Economy (Kemenparekraf), the Central Statistics Agency (BPS), and other relevant annual reports. The research results show that the COVID-19 pandemic has become a catalyst for accelerating digital transformation, expanding market reach, and increasing collaboration and creativity among the creative industries. In conclusion, although the COVID-19 pandemic presents many challenges, it has also provided a significant impetus for the growth of digital-based creative industries in Indonesia, creating opportunities that have the potential to change the landscape of the creative economy in the long term.